Synthesis of Copper Nanoparticles with Dragon Fruit (Hylocereus polyrhizus) Extract as a Bio-Reductor and Their Analysis Using a UV-Visible Spectrophotometer - Qomariyah, Ani; Hakim, Ardhi Khoirul (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Nanotechnology is a branch of science that investigates materials on a scale of 1-100 nanometers. One method that is often used to create copper nanoparticles is biosynthesis using plant extracts because it is more environmentally friendly, does not use toxic reagents and solvents and the process is simpler. Dragon fruit extract (Hylocereus polyrhizus) has potential as a reducing agent for metal compounds because it contains phenolic and carboxylic groups. This study aimed to synthesize copper nanoparticles (Cu-NPs) using a bio-reductor in the form of dragon fruit extract with various volume variations of CuSO4, pH variations, and stirring time variations. Red dragon fruit extraction was carried out by the maceration method to obtain extracts from dragon fruit, which were then used as a Cu metal-reducing agent. The resulting Cu nanoparticles were characterized using a UV-Visible Spectrophotometer. Based on the data, the highest absorbance value was obtained from the most volume of CuSO4, namely 2 mL with an absorbance peak at a wavelength of 700-750 nm. The optimum pH was obtained at pH 6 with a peak absorbance at a wavelength of 750 nm. The most effective time to obtain the absorbance peak at a wavelength of 700 nm was 15 min.